2007
DOI: 10.1093/chemse/bjm034
|View full text |Cite
|
Sign up to set email alerts
|

Taste Solution Preferences of C57BL/6J and 129X1/SvJ Mice: Influence of Age, Sex, and Diet

Abstract: To examine whether age influences taste solution preferences, we measured taste preferences of C57BL/6J and 129X1/SvJ mice given a series of 48-h 2-bottle tests with a choice between water and one of the following taste solutions: 2 mM saccharin, 5 mM citric acid, 30 microM quinine hydrochloride, 75 mM sodium chloride (NaCl), 10 mM inosine monophosphate (IMP), 50 mM calcium chloride (CaCl(2)), and 10% ethanol. We tested separate groups of male mice fed Teklad 8604 chow at ages 4, 6, 9, 12, 15, 20, 25, 30, 40, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 65 publications
5
30
0
Order By: Relevance
“…For example, out of a total of 40 mouse strains, 32 had no sex difference in sodium preference and 29 had no sex difference in calcium preference (82,85,86). Thus, sex differences in taste preferences are the exception rather than the rule in our laboratory.…”
Section: Discussionmentioning
confidence: 77%
“…For example, out of a total of 40 mouse strains, 32 had no sex difference in sodium preference and 29 had no sex difference in calcium preference (82,85,86). Thus, sex differences in taste preferences are the exception rather than the rule in our laboratory.…”
Section: Discussionmentioning
confidence: 77%
“…To determine if differences in age were likely to influence taste preferences we tested B6 and 129 mice aged between 6 and 125 weeks. We found that, with few exceptions, age made no difference to taste preferences [86].…”
Section: Choosing a Phenotypementioning
confidence: 55%
“…In concentrationpreference studies, the additional benefit of multiple tests was sufficient to outweigh the slight advantage of 96-h over 48-h tests. We also compared the taste preferences of mice fed with six different maintenance diets (four forms of cereal-based "chows" and two semisynthetic diets) and found that diet had little concerted effect on the variability of most two-bottle choice tests, although in some cases it had a large influence on strain means [ [94]; see also [86]]. Based largely on the fact that the ingredients of chow diets are unknown and variable, and thus experiments using them cannot be replicated, we decided the best diet for our purposes was AIN-76A [1,32], a semisynthetic diet recommended by the American Institute of Nutrition (now called the American Society for Nutrition).…”
Section: Choosing a Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Length, width and area were measured on each taste bud utilizing Image J software. Tests between deionized water and sodium saccharin are used to test for sweet, citric acid solution is used to test for sour, quinine hydrochloride (QHCL) and sucrose octaacetate (SOA) are used to test for bitter, NaCl is used to test salty taste preference, whereas inosine monophosphate (IMP) is used to test umami (Tordoff 2007). In the two bottle preference test, animals are given 48 hours with deionized water and a tastants solution.…”
Section: Scanning Electron Microscopementioning
confidence: 99%